Estabelecimento Individual de Responsabilidade Limitada – Algumas Reflexões (De Legibus - Law Journal, 2022)
The difference, in legal-dogmatic terms, between the commercial establishment (or company) and the assets of its proprietor, whether the latter is an individual trader (Article 13(1) of the Commercial Code) or a commercial company (Article 13(2) of the same Code), seems to be pacific. The aim of this article is to determine whether, in the case of the (inappropriately) named “Limited Liability Individual Establishment” (EIRL), which presupposes the existence of a separate patrimony within which it has been organised or set up, the same difference between the two subsists (scilicet: between commercial establishment and patrimony). The subject of the article is also the question of who is a trader in the case of the EIRL, given that the EIRL, or rather the separate assets into which it is organised or set up, do not have legal personality
Keywords: Limited Liability Individual Establishment (EIRL); business establishment and subject’s assets; separate assets; status as a trader.